A Quantitative and Qualitative Study on Patient and Physician Perceptions of Nephrology Telephone Consultation During COVID-19. (January 2022) - Heyck Lee, Seung; Ramondino, Sonya; Gallo, Kerri; Moist, Louise M.
Background: COVID-19 required rapid adoption of virtual modalities to provide care for patients with a chronic disease. Care was initially provided by telephone, which has not been evaluated for its effectiveness by patients and providers. This study reports patients' and nephrologists' perceptions and preferences surrounding telephone consultation in a chronic kidney disease (CKD) clinic. Objective: To evaluate patient and physician perspectives on the key advantages and disadvantages of telephone consultations in a nephrology out-patient clinic setting. Design: Cross-sectional observational survey study. Setting: General nephrology clinic and a multidisciplinary kidney care clinic in London, Ontario, Canada. Participants: Patients with CKD who were fluent in English and participated in at least one telephone consultation with a nephrologist during the COVID-19 pandemic. Methods and measurements: Nephrologists' and participants' input facilitated the development of both patient and nephrologist surveys. Participants provided self-reported measures in 5 domains of satisfaction: user experience, technical quality, perceived effectiveness on well-being, perceived usefulness, and effect on interaction. Nephrologists provided self-reported measures within 6 categories: general experience, time management, medication changes, quality of care, job satisfaction, and challenges/strengths. Descriptive statistics were used to present data. Content analysis was performed on 2 open-ended responses. Results: Of the 372 participants recruited, 235 participated in the survey (63% response). In all, 79% of the participants were ≥65 years old and 91% were white. Telephone consultation was a comfortable experience for 68%, and 73% felt it to be a safer alternative during the pandemic. Although 65% perceived no changes to health care access, most reported spending less time and fewer resources on transit and parking. Disadvantages to telephone consultation included a lack of physical examination and reduced patient-physician rapport. Eleven of 14 nephrologists were surveyed, with most reporting confidence in the use of telephone consultation. Physician barriers to telephone consultation included challenges with communications and lack of technology to support telephone clinics. Limitations: Our survey included a majority of older, white participants, which may not be generalizable to other participants particularly those of other ages and ethnicity. Conclusion: Although both patients and nephrologists adapted to telephone consultations, there remain opportunities to further explore populations and situations that would be better facilitated with an in-person visit. Future research in virtual care will require measurement of health care outcomes and economics. Trial registration: Not applicable as this was a survey.